2010
DOI: 10.2747/0272-3646.31.2.172
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Average Snow Depth Across the Western United States

Abstract: A network of cooperative observation stations was used to examine trends in average snow depth across the western United States. This station network includes a greater number of low-to moderate-elevation stations, where the snow is particularly sensitive to temperature changes, than the snow course and SNOTEL datasets used in other studies. Results indicate a widespread decrease in snow depth across the region; 70% of stations with statistically significant trends (p ≤ 0.5 or p ≤ 0.10) exhibit negative trends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…The regions where winter temperatures hover well below this band will likely not experience this strong trend because snow will still form, and regions with average temperatures well above this band will still see most of their precipitation as rain, with the occasional (less frequent) snow. This physical mechanism agrees with arguments in the literature [ Dettinger and Cayan , 1995; Knowles et al , 2006; Das et al , 2009; Grundstein and Mote , 2010; Mote et al , 2008]. In general the previous studies find that middle altitudes are the most sensitive, here we argue that there is also a strong latitudinal component to the sensitivities, and southern regions within the basin experience strong snowfall trends at high elevations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The regions where winter temperatures hover well below this band will likely not experience this strong trend because snow will still form, and regions with average temperatures well above this band will still see most of their precipitation as rain, with the occasional (less frequent) snow. This physical mechanism agrees with arguments in the literature [ Dettinger and Cayan , 1995; Knowles et al , 2006; Das et al , 2009; Grundstein and Mote , 2010; Mote et al , 2008]. In general the previous studies find that middle altitudes are the most sensitive, here we argue that there is also a strong latitudinal component to the sensitivities, and southern regions within the basin experience strong snowfall trends at high elevations.…”
Section: Discussionsupporting
confidence: 92%
“…In this region, snow acts as the largest storage of precipitation in the winter, with release of water during the critical spring and summer months [ Mote et al , 2005]. Observations over the past 50 years show a decrease in April 1 snow water equivalent (SWE) and a shift to earlier onset of snowmelt‐driven streamflow in both the Upper and Lower Colorado River Basins [ Mote et al , 2005; Grundstein and Mote , 2010; Stewart et al , 2005]. However, high‐elevation stations in the Rocky Mountains of Colorado show no trends or positive trends for the SWE and the timing of streamflow [ Mote et al , 2005; Stewart et al , 2005].…”
Section: Introductionmentioning
confidence: 99%
“…These include a warming climate, changes in precipitation, an accelerated nitrogen cycle, and invasions by non‐native species. These forces of change have become increasingly evident in recent years (Overpeck and Udall 2010), and their effects, as highlighted in Wilcox (2010), are seen in (i) changing patterns in snow accumulation and melt (Grundstein and Mote 2010; Regonda et al. 2005); (ii) increasing frequency and intensity of fires (Westerling et al.…”
Section: Understanding a Changing Landscape: A Research Imperative Fomentioning
confidence: 99%
“…Studies that have examined temporal trends in snowpack provide insight into the effects of temperature and precipitation on snowpack. Numerous empirical and model‐based studies have found strong evidence of negative temporal trends in snowpack within the western US, including Oregon (Hamlet et al , 2005; Knowles et al , 2006; Mote, 2006; Barnett et al , 2008; Casola et al , 2009; Grundstein and Mote, 2010). This includes not only declines in 1 April SWE, but also trends in earlier snow melt, earlier peak stream flows, and reduced stream flow.…”
Section: Methodsmentioning
confidence: 99%
“…However, these two factors are differentially important at different locations. Increased temperatures, which have the dual effect of reducing the proportion of precipitation that occurs as snow and increasing the amount of snow melt, have a larger impact at lower elevations and on the Pacific coast, where temperatures are closer to freezing (Hamlet et al , 2005; Knowles et al , 2006; Mote, 2006; Grundstein and Mote, 2010). Higher elevation locations, such as the Sierra Nevada and the Rockies, are cold enough that warming trends have not impacted snowpack, and so temperature is less of a factor.…”
Section: Methodsmentioning
confidence: 99%